SISTEM INFORMASI INVENTORY PADA YAYASAN GENERASI SEHAT INDONESIA SEHAT (SIIGESIT) TANGERANG SELATAN - Achyar Ibnu Hadjar; Duwi Cahya Putri Buani (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2019)
Yayasan Generasi Sehat Indonesia Sehat (GESIT) is a foundation that provides health equipment such as medicines to schools that have programs Klinik Sekolahku is a program from Yayasan GESIT. Schools are collaborating to make Yayasan GESIT need an information system that can simplify, curb the recording of inventory data, therefore an information system is created that can handle these problems. This system is called SIIGESIT or Sistem Informasi Inventory Yayasan Generasi Sehat Indonesia Sehat. SIIGESIT is designed using the RAD Model (Rapid Application Development) which is one of the software development models. The advantages of the RAD Model are that in the User Analysis stage it is involved in analyzing the needs and if the user agrees the second stage, namely the new system can be implemented so that the possibility of a miss occurs between analysts, programmers and users.